THU0270 Homocysteine, antiphospholipid antibodies and risk of vascular events in patients with systemic lupus erythematosus. (15th June 2017) - Stojan, G; Fu, W; Petri, M
Abstract : Background: SLE patients have higher plasma total homocysteine concentrations compared to healthy controls. Hyperhomocysteinemia in SLE is a potentially modifiable, independent risk factor for stroke and thrombotic events, hypertension, and coronary artery calcification. Objectives: We investigated the association of homocysteine levels with the presence of antiphospholipid antibodies as well as the potentially additive thrombotic risk in patients with antiphospholipid antibodies who have hyperhomocysteinemia. Methods: To analyze the association between hyperhomocysteinemia and the presence of antiphospholipid antibodies in SLE, 844 patients with homocysteine measurements were included in the analysis. 237 patients had at least one measurement over 15 umol/L. Patients were followed quarterly after cohort entry. The association of hyperhomocysteinemia with antiphospholipid antibodies is detailed in Table 1 . To analyze the prevalence of vascular events among SLE patients with antiphospholipid antibodies based on homocysteine levels, 571 patients with positive antiphospholipid antibodies and at least one homocysteine measurement were included in the analysis. There were 166 patients with at least one homocysteine measurement over 15 umol/L. The lupus anticoagulant was assessed by dRVVT with mixing studies and confirmatory tests. Anticardiolipin and anti-beta2 glycoprotein 1 were measured by ELISA (INOVA). Vascular events were defined as stroke, myocardial infarction, digital gangrene, and deep vein thrombosis. Results: Conclusions: SLE patients with elevated homocysteine were less likely (p<0.05) to have any of the antiphospholipid antibodies. Among patients with SLE who have antiphospholipid antibodies, elevated homocysteine is associated with a significantly higher prevalence of myocardial infarction and deep vein thrombosis (p<0.05). Disclosure of Interest: None declared